A new paradigm of injury intentionality. Issue 1 (1st March 1999) - Cheng, Tina L; Wright, Joseph L; Fields, Cheryl B; Brenner, Ruth A; Schwarz, Donald; O'Donnell, Regina; Scheidt, Peter C
Abstract : Objective —To improve understanding of processes leading to injury and assess more specifically the degree of intentionality. Methods —A new paradigm was developed that characterizes the act of inflicting injury (self, other, not inflicted) and the motive. Motives are determined for the act of injury and for the outcome. To test this, 986 cases of adolescent injuries in seven hospitals were reviewed. Three investigators independently classified all cases using the new paradigm and three used standard definitions of intent. Inter-rater reliability was measured. Results —Of injuries inflicted by others, 61% were intentional using the standard classification. In the new paradigm 67% were intended acts and 59% involved intentional motive for outcome. Altogether 87% of sports injuries were coded as unintentional acts compared with 96% using standard methods. Using standard classification there was 93% agreement between paired raters, with an average κ of 0.86. In the new paradigm questions on intentionality of act, outcome, and infliction of act, the agreement was 89%, 91%, 88%, with a κ of 0.79, 0.80, 0.76, respectively. Conclusions —This paradigm defines a spectrum of injury intent, enhances understanding of the causal sequence of injury, and has important implications for research and prevention.